A Cross-Sectional Survey of Risky Travel and Leisure Behaviors During the COVID-19 Pandemic. (1st September 2021) - Maddock, Jay E.; Suess, Courtney
Purpose: COVID-19 is largely spread through close contact with infected people in indoor spaces. Avoiding these spaces is one of the most effective ways to slow the spread. This study assessed who had engaged in risky travel and leisure behaviors before the availability of vaccines. Design: National cross-sectional on-line survey collected in November and December 2020. Setting: United States; Participants: 2589 adults representative by gender and race/ethnicity to the US population; Measures: The survey assessed if people had resumed 11 risky behaviors during the pandemic, prior to vaccines. Independent variables included age, race/ethnicity, region of the country, education, income, preexisting conditions, perceived severity and susceptibility, positive COVID diagnosis, and political ideology. Analysis: Univariate analysis and logistic regressions were used to assess demographic and psychological factors of those resuming these behaviors. Results: Most (60.3%) of people had resumed at least 1 behavior with eating inside of restaurants (33.2%) and visiting family and friends (37.5%) being the most prevalent. In the multivariate analyses, perceived susceptibility was significant across all behaviors. Young people, fiscal conservatives, and people with higher perceived severity were more likely to perform several of the behaviors. Preexisting conditions did not predict any of the behaviors. Conclusions: Travel and leisure behaviors vary by type of risk and may need specific tailored, prevention messages to promote risk reduction during future pandemics.